R. M. BALLANTYNE’S THE CORAL ISLAND: NEGOTIATING MASCULINITY, NATION AND THE EMPIRE - Meiling, Bhoomika (ShodhKosh: Journal of Visual and Performing Arts, 2022)
R.M Ballantyne’s writings were seen as greatly influential in forging an understanding of juvenile masculinity that involved views on supremacy of Christian, British young men involved in the colonial enterprise. As an influence on Boys Own para-literary material, The Coral Island reinforces this view of a just and Christian Empire. This paper examines these connections between the nation, the empire and the working class boy.